OS GÊNEROS DE TEXTO INSTANCIADOS EM LIVROS DIDÁTICOS DE LI E SUA RELAÇÃO COM OS CINCO EIXOS ESTRUTURANTES DA LÍNGUA INGLESA DA BNCC - Vasconcellos, Érica Tex de (2021)
This study aims to discuss how the five structuring axes of the National Common Curriculum Base (BNCC) and their skills are related to activities associated with text genres in English textbooks (LDLI). This research stands out as a document analysis with a qualitative approach. To carry out the research, we present the National Textbook Plan (PNLD) and the BNCC which guide the work of teachers and mediate the teaching-learning process in the curriculum components. We note the importance that the National Curriculum Parameters (1998) and the BNCC provide English language learning. In the postulates on the BNCC we identified the five structuring axes of the English language that help in promoting the student's linguistic literacy. In this educational context, we present the Foreign Language teaching methods according to Brown (1994), Harmer (2007) and Larsen-Freeman (2000) for understanding foreign language learning. After making these theoretical presentations, we postulate about the denomination of text genres according to Marcuschi (2008) and the theories of text genres according to Marcuschi (2008); Rodrigues (2014); Rojo (2005); Medeiros and Tomasi (2017) and Motta-Roth (2008). This research is composed of the analysis of a chapter in two didactic books of English Language of Elementary Education available in public schools of the city of Santa Maria-RS. The results obtained in this work dealt with the concentration of activities in only two structuring axes in one of the books and the diversity of activities in the five structuring axes in the other analyzed book. Finally, it is worth mentioning the importance of analyzing textbooks according to BNCC postulates to assist teachers in the selection of textbooks so that they meet the expectations and needs of students in learning the English language.